Bangla speech to text conversion using CMU sphinx - Bristy, Israt Jerin; Shakil, Nadim Imtiaz; Musavee, Tesnim; Choton, Akibur Rahman (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.